2012
DOI: 10.1155/2012/580696
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T-Cell-Independent Antibody Response Reduces Enterovirus 71 Lethality in Mice by Decreasing Tissue Viral Loads

Abstract: Enterovirus 71 (EV71) has induced fatal encephalitis in hundreds of thousands of infants and young children in the Asia-Pacific region since the past decade. Lymphocyte and antibody responses have been suspected to aggravate EV71-induced neurological symptoms, so anti-inflammatory agents have been used to treat patients with neurological symptoms. In the present study, we found that mice deficient in CD4+ T cells were resistant to EV71 infection as wild-type mice, whereas mice deficient in B cells were highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
(36 reference statements)
5
14
0
Order By: Relevance
“…However, we found that deficiency of B cells, but not CD4 T cells, abolished the protective effect of Flt3 ligand, suggesting that innate B cells, but not T helper cells, might contribute to Flt3 ligand-mediated protection in our model. These results are consistent with our previous report demonstrating that CD4 T cell-deficient mice can produce neutralizing antibodies to protect mice from EV-A71 infection possibly through innate B cells 31 . Our additional results showing the failure of Flt3 ligand to increase the production of T helper 2 cytokines (IL-4 and IL-5) in EV-A71-infected mice (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 93%
“…However, we found that deficiency of B cells, but not CD4 T cells, abolished the protective effect of Flt3 ligand, suggesting that innate B cells, but not T helper cells, might contribute to Flt3 ligand-mediated protection in our model. These results are consistent with our previous report demonstrating that CD4 T cell-deficient mice can produce neutralizing antibodies to protect mice from EV-A71 infection possibly through innate B cells 31 . Our additional results showing the failure of Flt3 ligand to increase the production of T helper 2 cytokines (IL-4 and IL-5) in EV-A71-infected mice (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Although cellular immune response has been confirmed an important role in the disease of HFMD, some of the immune mediators identified here are also important for an effective B cell-mediated humoral response, including neutralizing antibody production [18], [19]. We examined EV71 VP-1–specific IgG and IgM antibody levels in patient plasma.…”
Section: Resultsmentioning
confidence: 95%
“…Tonsils are an important site outside the CNS for viral replication in HFMD [17] , thus viral genomic load in throat swabs theoretically correlates with viral burden. In animal models, EV-A71 viral load is lower in surviving animals [ 18 , 19 ]. Therefore, we hypothesised that increasing viral load measured in throat swabs would correlate with the clinical severity of HFMD.…”
Section: Discussionmentioning
confidence: 99%